2016
DOI: 10.18632/oncotarget.10079
|View full text |Cite
|
Sign up to set email alerts
|

Metformin mediates resensitivity to 5-fluorouracil in hepatocellular carcinoma via the suppression of YAP

Abstract: Metformin plays an anti-proliferative role in tumor cells in many types of cancer. However, the correlation between metformin and sensitivity to chemotherapeutic agents in hepatocellular carcinoma (HCC) and the relevant mechanism are unclear. The present study showed that HCC patients with type 2 diabetes mellitus benefited from metformin administration, with a longer overall survival. Metformin resensitized Bel-7402/5-fluorouracil (Bel/Fu) cells to 5-fluorouracil (5-Fu) in vitro and in vivo, and the combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 40 publications
3
31
0
1
Order By: Relevance
“…Accumulating evidence has confirmed that metformin may inhibit cell migration or potentiate the effect of chemotherapeutic agents (30)(31)(32). Numerous studies have also demonstrated that metformin regulates the AMP-activated protein kinase and extracellular signal-regulated kinase pathways, and reverses drug resistance (33,34).…”
Section: Hif-1α Expression -----------------------------------mentioning
confidence: 99%
“…Accumulating evidence has confirmed that metformin may inhibit cell migration or potentiate the effect of chemotherapeutic agents (30)(31)(32). Numerous studies have also demonstrated that metformin regulates the AMP-activated protein kinase and extracellular signal-regulated kinase pathways, and reverses drug resistance (33,34).…”
Section: Hif-1α Expression -----------------------------------mentioning
confidence: 99%
“…These characteristics make YAP an attractive therapeutic target in cancer treatment. In HCC, YAP has been revealed to be involved in proliferation, migration, invasion and drug resistance (13)(14)(15). However, the underlying mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to immune checkpoint inhibitors such as pembrolizumab, metformin has been shown to reverse immune exhaustion . Interestingly, metformin has been shown to potentiate the anticancer effects of other drugs, including antimetabolites and tyrosine kinase inhibitors …”
Section: Discussionmentioning
confidence: 99%
“…70,71 Interestingly, metformin has been shown to potentiate the anticancer effects of other drugs, including antimetabolites and tyrosine kinase inhibitors. 72,73…”
Section: Discussionmentioning
confidence: 99%